The Students' Perception on Grade-Point Average (GPA) Score in Online Learning - Isvina Unaizahroya; Faiza, Dinar; Mayekti, Meilina Haris (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2024)
The purposes of this research were to identify the students’ perception on GPA score in online learning in English Language Education study program of Universitas Nahdlatul Ulama Purwokerto, and to analyze the students’ perception of the factors affecting English Language Education’s batch 2019 of Universitas Nahdlatul Ulama Purwokerto GPA score. The subjects of this research were 20 students of English Language Education Study Program, academic year 2019/2020 that are active until the 4th semester, as proved by GPA score that not get zero score. The type of this research is qualitative research with descriptive approach. The instruments of data collection were documentation (in the form of GPA score) and interviews by Google Meet. Based on the result, there were increased and decreased score. According to the result of GPA score, there are several conditions. First, the students got GPA score and the ability increased. Second, the GPA score increased but the ability decreased. Lastly, the GPA score and the ability decreased. Meanwhile, the factors that affected students’ GPA score were divided into two factors, internal and external. Internal factors included students’ health, motivation, passion, talent and students’ readiness. Meanwhile, the external factors included school environment and family motivation.